The library in Alexandria and the Bible in Greek - Collins, Nina L. (Supplements to Vetus Testamentum, 2000)
This work covers the translation of the Bible into Greek. Ancient evidence reveals that the earliest, written translation of the Bible in Greek was completed in Alexandria in 281 BCE, probably by 71 scholars, invited especially from Judaea by Ptolemy II.